The public function, organization and addressing: essential foundation in public administration - Turizo-Tapias, Héctor (EFIM Ediciones, 2019)
The present topic examines the place of the public function in the organization and direction within the public administration, in its constitutional commitment to respond to the fulfillment of the essential ends and purposes of the State, axis of its activity, seeking the important and sufficient articulation and management between public employment and the people that comprise it. For this, we analytically argue the regulations in this regard, the recommendations of writers on the subject, the manuals of functions as a tool for managing human talent and the Ibero-American Charter of the public function. This commitment is of such importance for the public administration, since the public function occupies in our Constitution a little more than half of its articles, so it seeks to detail not only the public function itself, but the essential foundation that it contains within the public administration to achieve the ends.